INTEGRASI TEKNOLOGI PENGAWETAN ALAMI KOMBINASI PERTANIAN PERAIRAN KELOMPOK NELAYAN RAJA PULAU DENGAN KEARIFAN LOKAL DAN BERKELANJUTAN - Sari, Selly Ratna; Susanti, Laili; Pratama, Rini Mustikasari Kurnia; Alvin, Alvin; Alghifari, Reza (Universitas Mataram, 2025)
The program purposed to enhance the capacity and independence of fishermen in processing marine products sustainably, healthily, and with added value. Through the application of natural preservation technology, marine products are processed using biopreservative materials derived from local aquatic agricultural resources, thereby extending shelf life without reducing nutritional quality. The program also emphasizes the integration of fisheries, aquatic agriculture, and nutritional aspects to produce high-quality food products and support food security in coastal communities. The implementation methods include socialization, training, production assistance, and evaluation of technology application. The outcomes demonstrate a transformation of the Raja Pulau fishermen’s group toward innovative, environmentally friendly, and market-oriented agroindustry. Significant improvements are reflected in product diversification, the development of functional products, and the group’s ability to produce alternatives beyond fresh fish. The use of ice as a preservative has also been substituted with natural alternatives such as gambier, carrageenan, torch ginger, and chitosan, which the community has learned to apply. These innovations not only improve fishermen’s knowledge and skills but also contribute to increased income. The products developed through this program have been marketed both within Bengkulu and beyond, providing tangible contributions to strengthening the blue economy based on local wisdom and supporting the vision of Golden Indonesia 2045